Duodenal Duplication Cyst: A Rare Case Report (Indian Journal of Case Reports, 2016)
Gastrointestinal duplication cysts are infrequent congenital abnormalities. 2% to 12% of these abnormalities are localized in correspondence of the duodenum. This disease rarely remains asymptomatic until adulthood. We present a case of A 62-year-old woman with intermittent upper abdominal pain and nausea, describing the diagnostic and therapeutic route.